Evaluating the Quality of Health Services for BPJS Nasional Indonesia Beneficiaries Using the Servqual Model - Sudirman; Yulia Safitri; Desak Eka Susianawati; Ake Royke Calvin Langingi; Jumain (The Indonesian Institute of Science and Technology Research, 2026)
Evaluating the quality of health services for BPJS participants is essential to ensure the effectiveness and sustainability of the National Health Insurance program. Although patient visits at the Tinggede Community Health Center have continued to rise, this increase has not been matched by improvements in service quality, highlighting the need for a structured assessment of patient needs. This study aims to evaluate patient perceptions of service quality using the ServQual model, which consists of five key dimensions: Reliability, Responsiveness, Assurance, Empathy, and Tangible. A quantitative cross-sectional design was employed involving 96 BPJS beneficiary respondents. Data were collected through a Likert scale–based questionnaire and analyzed using the Friedman test to compare perceptions across dimensions. Results show that Assurance and Responsiveness received the highest ratings, while Tangible scored the lowest and differed significantly from the top two dimensions. These findings indicate that non-physical elements, particularly competence, trustworthiness, and timely responses from healthcare workers, play a greater role in shaping patient satisfaction than physical facilities. The study contributes empirical evidence on priority areas for improving service quality in primary health care settings. Practical implications include enhancing staff competencies, streamlining service flow to reduce waiting times, and strengthening empathetic communication. The study concludes that efforts to improve service quality should prioritize non-physical dimensions that have the strongest influence on patient experience. Recommendations include ongoing quality evaluations, broader adoption of digital services, and expanding future studies to different regions and populations to deepen understanding of service quality determinants.